Mergers and acquisitions risk modeling - Yulia Vertakova; Inga Vselenskaya; Vladimir Plotnikov (Journal of Risk and Financial Management, 2021)
In the context of the dynamics of the modern external environment, the importance of risk management in general and the risks inherent in the processes of mergers and acquisitions has sharply increased. This is becoming one of the primary challenges in business, the solution of which will contribute to economic growth and development. In this article, based on a broad review of literature, the key risks of mergers and acquisitions are identified and classified, the level of their significance is assessed, the relevant management tools are selected for each risk and a computer program is developed that implements the selection of tools for each specific merger and acquisition transaction. A comprehensive automated methodology for the selection of risk management tools in the implementation of mergers and acquisitions can become an effective risk management tool for companies participating in such transactions. This will allow to identify and track risks in a timely manner, assess their significance, and, among other things, contribute to the adoption of effective management decisions regarding risk management.
Keywords: 330; risk management; mergers and acquisitions; model automation; risk management methodology; risk management tools